Warning that a three degree rise in temperature will 'cancel out' european emission reduction efforts. (Research'eu results magazine)
As a debilitating heat wave, nicknamed 'Lucifer' by the press, currently engulfs southern Europe, a new study part-supported by two EU-funded projects has warned that a rise in global temperatures of three degrees would reverse Europe's dedicated efforts to reduce ozone pollution.